The impact of the application of comprehensive quality standards on the performance of hospitals in The Kingdom of Saudi Arabia - Tayb, Maysa Ehsan (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to apply total quality standards as a method to improve performance, and the study was applied to Al-Noor Hospital in Makkah Al-Mukarramah. The study relied on the analytical descriptive approach, and the questionnaire was used as an appropriate tool for this research. The researcher reached a number of results, the most prominent of which are: The existence of an effect in the application of comprehensive quality standards on performance at Al-Noor Specialist Hospital at a high level on all criteria (leadership - beneficiary satisfaction - improving the quality of services - operations management), and the level of job performance in the hospital is relatively high. The study reached a number of recommendations, the most important of which are: spreading the culture of total quality and its concepts to all hospital workers to accept the requirements and standards of total quality.
Keywords: quality; total quality; total quality standards; hospitals; performance